2022
DOI: 10.1002/chem.202201781
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Effect of the Adsorption Preference of Additives on the Anisotropic Growth of ZSM‐5 Zeolite

Abstract: Zeolite morphology plays a crucial role in affecting catalytic performance, while is persistently challenging to tailor through crystal anisotropic growth. It has been recognized that specific additives can be introduced into the synthesis of zeolites to achieve anisotropic growth, however their role and the underlying mechanism are not well understood. Herein, the effect of eight specific additives on the anisotropic growth of the ZSM-5 zeolite is unveiled within the framework of crystallization engineering. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In previous studies, some researchers have reported that when the additives were introduced into the starting gel, they would interact with exposed silicon hydroxyl groups (Si-OH) on the specific crystal facets and tailor the anisotropic growth of zeolites. [33][34][35]44,45 Therefore, it can be inferred that CTA + may preferentially interact with the Si-OH groups on the [010] and [100] surfaces of zeolites, suppressing the crystal growth along the a-axis and b-axis to achieve the nanorod's c-axis oriented growth. Based on the above detailed discussion, it may be thought that the formation of bundle-like ZSM-5 nanorod assemblies goes through "crystallization and oriented growth by particle attachment", which is different from the classical seedinduced process (crystallization and growth by layer-by-layer).…”
Section: Formation Mechanism Of Zsm-5 Nanorod Assembliesmentioning
confidence: 99%
“…In previous studies, some researchers have reported that when the additives were introduced into the starting gel, they would interact with exposed silicon hydroxyl groups (Si-OH) on the specific crystal facets and tailor the anisotropic growth of zeolites. [33][34][35]44,45 Therefore, it can be inferred that CTA + may preferentially interact with the Si-OH groups on the [010] and [100] surfaces of zeolites, suppressing the crystal growth along the a-axis and b-axis to achieve the nanorod's c-axis oriented growth. Based on the above detailed discussion, it may be thought that the formation of bundle-like ZSM-5 nanorod assemblies goes through "crystallization and oriented growth by particle attachment", which is different from the classical seedinduced process (crystallization and growth by layer-by-layer).…”
Section: Formation Mechanism Of Zsm-5 Nanorod Assembliesmentioning
confidence: 99%
“…(a) Structure directing agent (SDA): The method of adding a SDA into aluminosilicate gel to synthesize mesoporous structure in situ is flexible and easy to operate, with little damage to the pore structure, and the diffusion of reactants or products can be specifically facilitated . Moreover, the use of a multifunctional SDA can also save raw materials.…”
Section: Strategies To Inhibit Carbon Depositionmentioning
confidence: 99%
“…To date, a variety of organic small compounds such as alcohols, lactams, ketones, and amino acids have been utilized as assisted additives or growth modifiers for the syntheses of various zeolites with specific morphology and porosity, including nanocrystal, lamellar, core–shell, hierarchical architecture and so on. 16–21 In particular, some common amino acids and their derivatives like arginine, carnitine and lysine have shown great advantages in modulating the shape and particle size of various zeolite crystals. 20–23 For instance, Rimer and his co-workers reported that the addition of amino acid arginine could help the formation of silicalite-1 ( MFI type) crystals with longer dimensions in the main direction of internal diffusion, possibly related to the fact that the growth modifier has the ability to impede nanoparticle addition.…”
Section: Introductionmentioning
confidence: 99%